Adequacy of Three Dimensional Miniplate In Treatment Of Mandibular Fracture In Interforaminal Region - Singh, Vivek; Giri, Ritesh (Journal of Chitwan Medical College, 2019)
Background: Mandible is one of the commonly fractured bone due to trauma, assault and falls. Treatment includes closed and open methods. Methods of open reduction and internal fixation have changed and diversified enormously in the past few years. Champy’s miniplate fixation, dynamic compression plating has become a standard approach. More recently, three dimensional miniplates have been developed by Farmand which may be effectively used in mandibular fractures. The aim of this study was to check the adequacy of three dimensional miniplate in management of mandibular fracture occurring in the interforaminal region.Methods: A prospective clinical study was carried out in patients attending Emergency Department and Department of Oral and Maxillofacial Surgery, Nobel Medical College and Teaching Hospital (NMCTH) suffering from mandibular fractures in interforaminal region from May 2018 to January 2019.Results: A total of 17 patients with 18 fracture in interforaminal region, all male were included in the study. The age ranged from 16 to 50 years with a mean of 29.17 ± 9.48. Road traffic accident was the leading cause of injury with 15 out of 17 patients (88.23%). There was no incidence of wound infection, wound dehiscence, malunion, nonunion, plate fracture within the follow up period of 3 months. One fracture was unstable on 1st postoperative day and also had mildly deranged occlusion which was managed with intermaxillary fixation for two weeks.Conclusions: Three dimensional plates fulfills the treatment goals of adequate stabilization and fixation of mandibular interforaminal fractures.